Increasing area under pulses and soil quality enhancement in pulse-based cropping systems - Retrospect and prospects - KAUR, RAMANJIT; SHIVAY, Y S; SINGH, GURIQBAL; VIRK, HARPREET KAUR; SEN, SUMAN; RAJNI, RAJNI (The Indian Journal of Agricultural Sciences, 2018)
India is the largest producer (25% of global production), consumer (27% of world consumption) and importer (14%) of pulses in the world (Anonymous 2016). Pulses accounted around 20% of the area under foodgrains and contribute around 7-10% of the total foodgrains production in the country. Productivity of pulses has improved by 65.07%, from 441 kg/ha in 1950-51 to 728 kg/ha in 2014-15. There is large scope to increase the area and production under pulses by utilizing existing rice fallows by growing chickpea, lentil, pea and khesari (lathyrus) after rice. But major hurdles in the successful cultivation of pulses in rice-fallows are the non-availability of quality seed, irrigation facilities, labour and other input availability. The production potential of pulses can be improved through introduction of short duration, nutrient responsive high yielding varieties and assured supply of quality seed, efficient nutrient management techniques and growth regulators, with supplemental irrigation. Declining factor productivity, depletion of soil fertility and over mining of native nutrient reserves, depletion of groundwater, increasing weed menace, and environmental pollution are major problems of rice-wheat cropping system. Introducing a legume (summer mungbean) in rice-wheat cropping system (RWCS) is one of the alternatives for overcoming some of these problems and provides additional economic returns and employment. Diversifying cropping systems with inclusion of pulse crops (mungbean or urdbean) can enhance soil water conservation, soil N availability, system productivity, soil physico-chemical properties such as aggregate stability, soil structure, bulk density and hydraulic conductivity, and soil biological activities. Moreover, levels of organic carbon, total N, available nitrogen, phosphorus, potassium and micronutrients increased significantly and substantially due to inclusion of mungbean in RWCS. Simultaneously the soil microbiological properties, viz. microbial biomass carbon, microbial biomass nitrogen and enzymatic (alkaline phosphatase, acid phosphatase, dehydrogenase, glucosidase, FDA hydrolysis, etc.) activities were also significantly higher in soils of rice-wheat-mungbean cropping system (RWMCS) than in RWCS. Therefore, this paper reviewed the inclusion of short duration pulses in different cropping systems in general and rice-fallows in particular which could help the farmers for getting the additional returns, besides improving soil physical, chemical and biological properties and help to sustain the agriculture productivity in the long-term.